Família cristã: espiritualidade, amor e violência - Velozo, Joel de Carvalho (2007)
For three decades I have been directly involved with the ecclesiastic Christian world closely and following undesirable behaviors that go beyond expectations in spiritual, loving and violent environments in spiritual environment, lovely and violent that happens frequently in Christians homes, which are omitted, hidden and ever concealed in the name of an ethic that I prefer to call cynical hypocrisy; so that when we report these facts its normal to say these things happen with people from the world, and never in the world of Christian people . The reality point to shadowy and controversial questions that for a long time have been swept under the carpet. Our purpose with this work is to discuss matters which relate to the realities of everyday life and which we cannot, by any means, pretend do not exist. Either we face up to attacking the causes and effects or we will be destroyed by this monster called violence.